2005
DOI: 10.1074/jbc.m508515200
|View full text |Cite
|
Sign up to set email alerts
|

CDK Phosphorylation Inhibits the DNA-binding and ATP-hydrolysis Activities of the Drosophila Origin Recognition Complex

Abstract: Faithful propagation of eukaryotic chromosomes usually requires that no DNA segment be replicated more than once during one cell cycle. Cyclin-dependent kinases (Cdks) are critical for the re-replication controls that inhibit the activities of components of the pre-replication complexes (pre-RCs) following origin activation. The origin recognition complex (ORC) initiates the assembly of pre-RCs at origins of replication and Cdk phosphorylation of ORC is important for the prevention of re-initiation. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…Even when regulation appears conserved, as has been noted in previous studies (22,23), we found that the numbers and positions of CDK consensus sites were not always conserved. A striking example of this is the linker region of ORC1, which contains a strong cluster of CDK consensus matches in all of the animals and most of the fungi (Figs.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…Even when regulation appears conserved, as has been noted in previous studies (22,23), we found that the numbers and positions of CDK consensus sites were not always conserved. A striking example of this is the linker region of ORC1, which contains a strong cluster of CDK consensus matches in all of the animals and most of the fungi (Figs.…”
mentioning
confidence: 50%
“…In addition, CDK target proteins often contain multiple CDK consensus sites closely spaced in their primary amino acid sequence; we refer to these as ''clusters.'' Previous studies have noted that, even when clusters of characterized sites are found in orthologous pre-RC components, the individual consensus sites are not always conserved in position or number (22,23). We refer to this as ''turnover'' of sites and suggest that it is consistent with regulation through mechanisms that impose loose constraints on spacing and number of phosphorylation sites (ref.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This behavior is reminiscent of ORC, whereby the specific binding of origins is known to regulate initiator ATPase activity (48,57). Given the phylogenetic kinship between cellular initiators, it seems likely Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases where specific phosphorylation sites have been identified, multiple phosphorylation events are required to remove the protein from chromatin, suggesting that there is a common mechanism for Cdk1-dependent hyperphosphorylation in the regulation of DNA replication. [4][5][6][7] Dbf4 degradation at the end of mitosis has previously been suggested as the major regulation mechanism in limiting the activity of the DNA replication activator Dbf4/Drf1-dependent kinase (DDK; Cdc7) function to S phase, at least in budding yeast. [8][9][10][11] This proposal was mainly based on the following observation: Although the level of yeast Cdc7 protein is relatively constant throughout the cell cycle, that of Dbf4 fluctuates as it is low in G1 and the post-metaphase/anaphase transition but high during S and G2 phases.…”
Section: Introductionmentioning
confidence: 99%